ANALISA TREN KINERJA KEUANGAN DAN VALUASI SAHAM PT ACE HARDWARE INDONESIA TBK: STUDI LONGITUDINAL 2019-2023 - Sabina Berlina Gulo; Agus Wibowo (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2025)
The increasingly competitive Indonesian capital market demands investors to be more meticulous in assessing company performance, not only through financial ratios but also trends over a specific period. This study aims to analyze the trends in financial performance and stock valuation of PT Ace Hardware Indonesia Tbk longitudinally during the 2019–2023 period, which includes the pre-, during, and post-COVID-19 pandemic phases. The research method used is descriptive and associative quantitative with secondary data from annual financial reports and stock prices. Data analysis includes descriptive statistics, classical assumption tests, and multiple linear regression. The results show fluctuations in financial performance, with profitability tending to recover post-pandemic, as well as volatility in stock valuation as reflected by PER and PBV. Although regression analysis indicated a consistent influence of the Debt to Equity Ratio (DER) on valuation, no variables were partially significant due to multicollinearity and sample limitations. The study concludes that the company demonstrated resilience in facing pandemic challenges, and highlights the importance of considering external factors and methodological limitations in interpreting results. The research implications contribute to investors and management in decision-making and provide a basis for further studies in the retail sector